Analisis Pembiayaan Akad Musyarakah pada Lembaga Keuangan Syari’ah di Indonesia: Studi Pendekatan NVivo dan Literatur Review - Maretha Ika Prajawati; Rohmadi; Doni Yusuf Bagaskara (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to determine financing analysis in sharia financial institutions in Indonesia using the NVivo approach. This research uses qualitative methodology with the Nvivo approach and literature review. "Data analysis techniques include: (1) mapping the number of news article codes based on qualitative analysis using Nvivo 14 software around the "Musyarakah Agreement", (2) mapping visualization results with hierarchical diagrams and testing the correlation between media articles using Nvivo 14 software; (3) mapping research topics with the World Cloud or a collection of words that are often discussed in media articles; and (4) testing the significant value between media articles to determine the size of the correlation around the topic "Musyarakah Agreement". The results of this research indicate that the topic that is often discussed in media articles regarding Musyarakah Contracts is the type and purpose of Musyarakah. Meanwhile, a topic that is rarely discussed by media articles regarding Musyarakah Agreements is the provisions and procedures for Musyarakah